Spirit Piagam Jakarta Dalam Undang-Undang Dasar 1945 - Mujar Ibnu Syarif (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2016)
Abstract: In the second trial BPUPKI, both nationalist and Islamic groups consensual that the future of Indonesia's independence will be based on the principle